The chancellor guide to the legal and Shari'a aspects of Islamic finance - Dar, Hymayon A.; Moghul, Umar F. (Chancellor Publications, 2009)
A professional reference book that focuses specifically on the legal dimensions of Islamic Finance. It brings together 19 Islamic Finance legal practitioners and advisors to provide a comprehensive legal perspective on the subject. It is suitable for those with a professional interest in Islamic Finance - be they lawyers, accountants, or bankers.